ELECTRIC POWER SUPPLY OF GUARD SIGNALING FROM HIGH-VOLTAGE LINE OF ELECTRICITY TRANSMISSIONS - Kostenko, V. O.; Smetanin, I. N.; Shcekotihin, O. V. (Radio Electronics, Computer Science, Control, 2014)
Vandal destruction supports existing power lines lead to the need for security systems supports. For this, there is must be the instrument power in units of watts on each mast. Literature review showed that it is a problematic issue. For Electric power transmission line at the level of kilowatts, and at the level of microwatts they use bulky heavy (hundreds of pounds) design, and a range of units watts they propose solution to the problem with the help of autonomous power supply system (solar, wind), which have several drawbacks. The authors propose a method PTO transmission line on each support, it ensures the withdrawal of energy from the high-grade zone in the low-grade-level units of watts, the constructive implementation of which does not exceed 50 kg, it’s compact and has a low cost. The novelty lies in the task of producing power in units of watts on each support of electric-power transmission new combination of known elements, changes in the design of insulators and supply of industrial release of a new product – solar panels in the form of vacuum tubes – «Alamp».